Sistem Informasi Penjualan Obat Berbasis Web pada Apotek Diana Menggunakan Algoritma Horspool - Rofi’ah , Isnaini; Hantoro , Kusdarnowo; Mugiarso , Mugiarso (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
Pharmacy is a means of pharmacy practice services carried out by pharmatics. Pharmatices provide various kinds of medicines that can be thought and sold with prescription and non-prescription. The purpose of this research is to ease the work of managing incoming and outgoing data from drug sales The medicines provided by pharmacies are certainly not small and will take a lot of time if the sales process and recording information still uses simple methods such as writing on a book. As is the case with the Diana pharmacy, in recording information still uses simple methods such as writing on a book. As is the case with the Diana Pharmacy, in recording drug information, they still use this method. This is course of outdated because it has now entered an era of increasingly sophisticated technology. Therefore, Diana Pharmacy requires an information system to overcome these problems and the application of the Horspool algorithm, namely string search and with the waterfall development method in the development of information systems.